A Madame Bovary’s Daughter: David Lean’s Visual Transliteration of Flaubert - Franck Dalmas (Flaubert: Revue Critique et Génétique)
If we want to consider Madame Bovary as an innovative work of art it is crucial to visualize Flaubert’s narrative strategy. The scholarship of Madame Bovary on film has scrutinized the many adaptations and how to relate them to the writing technique. Faithful versions rely on a ‘text-made-into-film’ equivalence where Flaubert’s intentions are limited to the authentic context. This article deems a different cinematic approach with a film that has not received full attention: Ryan’s Daughter by David Lean. The impersonal narration and sensual expression of the novel are reassessed in light of this loose adaptation. The analysis of key scenes and characters is envisaged from a counterpointing angle while matching a subtle evocation of Flaubert’s style.